2004
DOI: 10.1073/pnas.0405979102
|View full text |Cite
|
Sign up to set email alerts
|

Activated macrophages are an adaptive element of the colonic epithelial progenitor niche necessary for regenerative responses to injury

Abstract: We have identified cellular and molecular features of the stem cell niche required for marked amplification of mouse colonic epithelial progenitors (ColEPs) that occurs in response to wounding of the epithelium with dextran sodium sulfate. This regenerative response in areas adjacent to breaches in the epithelial barrier depends on the gut microbiota because ColEP proliferation is markedly diminished in germ-free animals. Analysis of conventionally raised C57BL͞6 (B6) knockout mice lacking the Toll-like recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
486
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(518 citation statements)
references
References 47 publications
25
486
0
7
Order By: Relevance
“…It has also been shown that a disruption of Tolllike receptor signaling causes an impairment of tissue repair by intestinal epithelial cells (Rakoff-Nahoum et al, 2004). Moreover, activated macrophages are important niche components for intestinal epithelial progenitors in regenerative responses (Pull et al, 2005). Therefore, it is conceivable that downregulation of miR-7 leads to suppression of differentiation, inducing the proliferation of undifferentiated epithelial cells in the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that a disruption of Tolllike receptor signaling causes an impairment of tissue repair by intestinal epithelial cells (Rakoff-Nahoum et al, 2004). Moreover, activated macrophages are important niche components for intestinal epithelial progenitors in regenerative responses (Pull et al, 2005). Therefore, it is conceivable that downregulation of miR-7 leads to suppression of differentiation, inducing the proliferation of undifferentiated epithelial cells in the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue macrophages are implicated in the proliferation of epithelial progenitor cells in the intestine 19 . We thus examined macrophage infiltration in the respective mutant mice by immunostaining.…”
Section: Macrophage Accumulation In Dysplastic Tumors and Preneoplastmentioning
confidence: 99%
“…3 Embryonic macrophages appear to play a positive trophic role that may have parallel reparative functions in many adult tissues undergoing repair and cellular replacement. 1,20 A number of studies have suggested that infiltrating macrophages along with the trophic factors they release participate in tissue repair of the kidney, 20 -22 brain, 23 skin, 24,25 lung, 26 liver, 27 heart, 28 gastrointestinal tract, 29,30 and skeletal muscle. 31,32 Indeed, the pleiotrophic roles for CSF-1 in reproduction, development of multiple organ systems, and maternal-fetal interactions during pregnancy by macrophage-mediated processes have also been well defined.…”
mentioning
confidence: 99%